2023
DOI: 10.1002/path.6167
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic SIRT1 promotes paclitaxel resistance in ovarian carcinoma through increased formation and survival of polyploid giant cancer cells

Abstract: Therapeutic resistance is a notable cause of death in patients with ovarian carcinoma. Polyploid giant cancer cells (PGCCs), commonly arising in tumor tissues following chemotherapy, have recently been considered to contribute to drug resistance. As a type III deacetylase, Sirtuin1 (SIRT1) plays essential roles in the cell cycle, cellular senescence, and drug resistance. Accumulating evidence has suggested that alteration in its subcellular localization via nucleocytoplasmic shuttling is a critical process inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…In addition, PRL-3 also promotes the formation of grossly hyperdiploid and multinucleated cancer cells known as polyploid giant cells (PGCCs), which typically appear in tumor tissue after chemotherapy, forming a stem cell-like pool that promotes cell survival, chemotherapy resistance, and tumor recurrence [ 141 , 142 ].…”
Section: The Relationship Between Prl-3 and Drug Resistancementioning
confidence: 99%
“…In addition, PRL-3 also promotes the formation of grossly hyperdiploid and multinucleated cancer cells known as polyploid giant cells (PGCCs), which typically appear in tumor tissue after chemotherapy, forming a stem cell-like pool that promotes cell survival, chemotherapy resistance, and tumor recurrence [ 141 , 142 ].…”
Section: The Relationship Between Prl-3 and Drug Resistancementioning
confidence: 99%
“…Consequently, the formation of PGCCs may be a significant cellular response to AURK inhibitors, potentially leading to treatment resistance or tumor recurrence. Recently, H. Xu et al found that Sirtuin1 (SIRT1), a type III deacetylase, is overexpressed in the cytoplasm and promotes drug resistance in ovarian cancer cells after paclitaxel treatment by increasing PGCC formation and allowing cells to escape senescence ( Xu et al, 2023 ). Additionally, cytoplasmic SIRT1 may play a role in polyploidization by promoting the binding of cyclin B and CDK1 ( Xu et al, 2023 ).…”
Section: Therapies Targeting Pgccsmentioning
confidence: 99%
“…Recently, H. Xu et al found that Sirtuin1 (SIRT1), a type III deacetylase, is overexpressed in the cytoplasm and promotes drug resistance in ovarian cancer cells after paclitaxel treatment by increasing PGCC formation and allowing cells to escape senescence ( Xu et al, 2023 ). Additionally, cytoplasmic SIRT1 may play a role in polyploidization by promoting the binding of cyclin B and CDK1 ( Xu et al, 2023 ). Ovarian cancer cells gain a survival advantage through polyploidization, which is a key mechanism for generating chemotherapy resistance.…”
Section: Therapies Targeting Pgccsmentioning
confidence: 99%